Leptosphaerulina species isolated from golf turfgrass in China, with description of L. macrospora, sp. nov. (3rd September 2021) - Liang, Junmin; Li, Guangshuo; Hou, Lingwei; Zhao, Meiqi; Cai, Lei
ABSTRACT: Leptosphaerulina leaf blight occurs on most turfgrasses. Hitherto, Leptosphaerulina species associated with this disease include L. americana, L. argentinensis, L. australis, and L. trifolii . However, following Koch's postulates, L. australis was confirmed as saprobes but not pathogens, and the other three species have not been tested. The pathogenicity of Leptosphaerulina spp. is still questionable. In this study, we isolated 19 Leptosphaerulina strains from diseased golf turfgrasses in China, and they were identified as L. gaeumannii, L. saccharicola, and a new species, L. macrospora, through multilocus (ITS, 28S, rpb2, and tub2 ) phylogenetic analyses and morphological observations. Pathogenicity test revealed that the three Leptosphaerulina species identified in this study cannot infect live/healthy turfgrass tissues of Poa pratensis and Agrostis stolonifera and only produced pseudothecia on the dead leaves of stressed seedlings. Considering the results of pathogenicity tests in this and previous studies, we speculate that most Leptosphaerulina species isolated from diseased turfgrass are not pathogens but saprobes. Applying proper management practices to prevent severe turfgrass stress is a key measure to reduce or eliminate the effects of Leptosphaerulina on golf turfgrass.